2021
DOI: 10.1097/ju.0000000000001811
|View full text |Cite
|
Sign up to set email alerts
|

Features of Various Bladder Lesions and Their Impact on Clinical Symptoms and Recurrence in Interstitial Cystitis

Abstract: Purpose: We aimed to investigate the impact of various bladder lesions on the clinical symptoms and recurrence of interstitial cystitis (IC). Materials and Methods: Patients with IC who underwent transurethral resection and cauterization for Hunner lesions (HLs) were enrolled. Features of HLsdnoninflamed, inflamed, and gradually inflameddand associated cystoscopic findings, including waterfall bleeding (none, focal or extensive), submucosal hemorrhage, and mucosal streak, were analyzed to investigate their ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…Although the criteria of the diagnosis is the confirmation of Hunner’s lesions by cystoscopy, the conditions under which cystoscopy is carried out must be carefully considered. Cystoscopy in the outpatient setting, where adequate bladder dilatation can be difficult, misses 10.9% of Hunner’s lesions 5 . Thus, the current diagnosis relies on subjective evaluation by cystoscopy, which might not be perfect, and we hoped to add an objective element to the diagnosis by establishing novel biomarkers in the present study.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Although the criteria of the diagnosis is the confirmation of Hunner’s lesions by cystoscopy, the conditions under which cystoscopy is carried out must be carefully considered. Cystoscopy in the outpatient setting, where adequate bladder dilatation can be difficult, misses 10.9% of Hunner’s lesions 5 . Thus, the current diagnosis relies on subjective evaluation by cystoscopy, which might not be perfect, and we hoped to add an objective element to the diagnosis by establishing novel biomarkers in the present study.…”
Section: Introductionmentioning
confidence: 98%
“…Cystoscopy in the outpatient setting, where adequate bladder dilatation can be difficult, misses 10.9% of Hunner's lesions. 5 Thus, the current diagnosis relies on subjective evaluation by cystoscopy, which might not be perfect, and we hoped to add an objective element to the diagnosis by establishing novel biomarkers in the present study.…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, there are no direct links between hematuria and life-threatening or symptomatic IC [22,23]. The former might be associated with smaller functional capacity of UB and urgency [24]. Since HLs were considered a sign of frequent recurrence [24], treating hematuria could be meaningful in preventing IC deterioration to some extent.…”
Section: Discussionmentioning
confidence: 99%
“…The former might be associated with smaller functional capacity of UB and urgency [24]. Since HLs were considered a sign of frequent recurrence [24], treating hematuria could be meaningful in preventing IC deterioration to some extent. A,B) The expressions of caspase-3 and Bax were higher in the IC group than in the treatment group, while the anti-apoptotic Bcl-2 was higher in the treatment group than in the IC group.…”
Section: Discussionmentioning
confidence: 99%
“…However, no placebo controlled clinical trials have demonstrated any benefit since the questionable pivotal trials 30+ years ago that showed no objective symptom changes, and only a 30% improvement on an unbalanced PORIS (Patient's Overall Rating of Improvement of Symptoms) scale that would no longer be considered valid for drug approval studies. 3,4 Subsequent U.S. Food and Drug Administration mandated phase 4 trials showed no dose response with triple the approved dose, 5 and no response over placebo. 6 With the growing literature on the increased risk of maculopathy associated with chronic administration and U.S. Food and Drug Administration black box warning regarding its use, it would seem this drug’s risk/benefit ratio should preclude its guideline recommendation in 2022.…”
mentioning
confidence: 99%